Representations of trauma from mass violence during Zimbabwe's liberation struggle in selected Zimbabwean literature. - Viriri, Advice (Africa Institute for Culture, Peace, Dialogue and Tolerance Studies., 2016)
This article is concerned with the mnemonics of colonial violence and how Chimurenga War during Zimbabwe’s liberation struggle has created far-reaching consequences derived from incidents of mass violence. It emphasises the genocidal quality of this colonial era’s murderousness. It is believed that many liberation struggles had strong genocidal overtones and it the purpose of this research to ascertain whether this notion captures this war. It assesses how freedom fighters and the masses dealt with the outbreak of mass violence and its immediate aftermath. The article further explores the presentation of trauma in selected Zimbabwean war literature, narratives which arc intensely embedded in psychological discourse, strewn with injured or suffering war-veterans whose personalities and reputations are not only altered but also affected by continually experiencing trauma throughout their lifetime. This chosen literature depicts realistic human descriptions of more severe moments in chivalric Chimurenga War life. The Chimurenga War was favourable to the deployment of extreme violence against the Rhodesian Forces whose retaliation where aimed at the Zimbabwean masses. This article demonstrates the various ways in which the genre’s imaginative possibilities contributes to the lasting effects of wounds from extremely violent Chimurenga War episodes that defy clear categorisation, but which fomented genocidal and other kinds of extreme violence from various contestants. Many advocates view this development of an enduring and shared memory of Chimurenga War events as an essential step to healing the wounds of a distressed Zimbabwean national conscience and preventing the recurrence of such mass atrocities symptomising through Zimbabwe’s post independence war traumas.